[Marcos ; Street children ; John Lesaca [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1989)
Taking a look at the hidden wealth of Marcos and what may happen in the event of his death. A story about Victor, a victim of child abuse, whon ran away from home and now lives in Manila streets. A jazz violinist who mixes the classical with the contemporary sound.
Marcos (15 min.) -- Street children (17 min.) -- John Lesaca (11 min.)
VHS.
Keywords: Marcos, Ferdinand Edralin -- 1917-1989.; Lesaca, John; Jazz musicians -- Philippines; Street children -- Philippines -- Manila